Interiors can address social justice: Fact or fiction - Smith, Dianne (Springer, 2014)
Interior architectural designs can influence the quality of a person’s day-to-day life. However, there is an apparent absence of such professionals practising within projects and policy development that relate to environments for members of our community who are considered to be without, or who are marginalized in either local or international contexts. Therefore issues of Social Justice are raised and the concept defined. People may be disadvantaged due to conditions beyond their immediate control—whether these conditions be medical, political, cultural or geographical. The key characteristics of interior architecture are discussed to demonstrate how practitioners and educators could contribute to improving the quality of lives of such people. As background to this proposition, a study to ascertain whether interior architecture is involved in socially sustainable projects and debates was undertaken in 2010. The question posed was: ‘what is the nature of the profession’s involvement and impact?’ This was answered in three ways. Firstly, the positioning statements of major professional design bodies were reviewed. Secondly, interior-based projects and the people involved were sought. Finally, literature from other fields was sourced to gain insights. The findings and their implications for the future directions of interior architecture are discussed in relation to the field of social sustainability. In response to the study’s outcomes, a snapshot is constructed which enables roles and strategies for interior architecture and associated designers to be formulated.